Berita Krjogja.Com Tentang Kelangkaan Oksigen Dalam Perspektif Komunikasi Risiko - Senja Yustitia (Jurnal Media dan Komunikasi Indonesia, 2022)
The incident of oxygen scarcity in DIY during PPKM Darurat was then widely discussed. It was also associated with the death of a COVID-19 patient at RSUP Dr. Sardjito. Many media reported this incident, one of which was krjogja.com. This research aims to explore aspects of risk communication in krjogja.com's reporting on oxygen scarcity. Researchers conducted a qualitative content analysis on 11 news related to events from 3-20 July 2021. This research shows that krjogja.com's news about oxygen scarcity during the PPKM Darurat period is not open, tends to be less accurate, and fails to provide various information. Thus, there is a gap between the information received by the public and what happened. From the perspective of risk communication, the news about oxygen scarcity during PPKM Darurat on krjogja.com is not adequate for risk assessment activities in the public.